2021
DOI: 10.1111/trf.16432
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the preparation method of red cell concentrates on transfusion indices in thalassemia patients: A randomized crossover clinical trial

Abstract: Background The average hemoglobin content of red cell concentrates (RCC) varies depending on the method of preparation. Surprisingly less data are available concerning the clinical impact of those differences. Study Design and Methods The effects of two types of RCC (RCC‐A, RCC‐B) on transfusion regime were compared in a non‐blinded, prospective, randomized, two‐period, and crossover clinical trial. RCC‐A was obtained by whole blood leukoreduction and subsequent plasma removal, RCC‐B removing plasma and buffy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In accordance with previously reported results [16], we measured a higher Hb content for P-RBCs prepared with method 1 (18-20% more than method 2). The RBCs count (18-23% more than method 2) and HCT levels increased accordingly.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In accordance with previously reported results [16], we measured a higher Hb content for P-RBCs prepared with method 1 (18-20% more than method 2). The RBCs count (18-23% more than method 2) and HCT levels increased accordingly.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent one-year crossover clinical trial [ 16 ], the procedure suggested by the Thalassemia International Federation (here method 1) was compared with another method routinely used to prepare P-RBCs for βTM patients [ 9 ], where whole blood is first separated to obtain packed erythrocytes, which are subsequently filtered (here method 2). Method 1 was proved to produce P-RBCs with a higher content of Hb, which in turn resulted in a longer transfusion interval (14.8 vs. 14.2 mean days between two consecutive transfusion episodes).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations